Meningkatkan Value Product, Pelaporan Keuangan Digital Dan Pemasaran Digital Pasca Covid 19 Pada UMKM Katering Darso - Made Wedaswari; Salman Faris Insani; Sari Widati; Siti Nur Annisaa’; Rihan Mustafa Zahri (Jurnal Informasi Pengabdian Masyarakat, 2023)
Sukoharjo is a district that has quite well-known names or nicknames, including: prosperous city, textile city, city of girls (trade, education, industry, and business), herbal medicine district, and so on. One of the industries run in Sukoharjo district is a home industry. The home industry is one manifestation of the existence of Small and Medium Enterprises (MSMEs) as a support for the Indonesian economy which contributes 23.89% to GDP and 93.78% to total employees. The development of the culinary world in Sukoharjo district is quite rapid. This is in line with the development of catering in the Sukoharjo district. For example, the MSME business in Darso catering is in Kwarasan, Grogol, Sukoharjo. Business competitors in the culinary catering business industry will be able to survive if they increase the value of their products. The management of Darso's catering business is still simple. Have not kept records of financial reports or bookkeeping in an orderly manner. These proposals together with the Community Service Team and partners will carry out training in management management starting with planning, implementing and supervising / controlling production activities in accordance with the expectations of business owners, namely being able to produce goods / products effectively and efficiently, so that business owners can guarantee survival and development, then it is appropriate if the company does the best management in the field of production. Since the Covid-19 pandemic took place, Darso's catering business has begun to redesign its business. During the pandemic, Darso catering owners started doing research. Solutions related to increasing product value by increasing new innovations such as improving service quality. Service quality can be improved by means of good and friendly service to consumers or customers of the catering business. Improving the quality of packaging or product containers produced. Maximizing the use of marketing tools, namely to identify consumer responses to products. Provide basic accounting training and assistance in making simple general journals to profit and loss reports. Financial management and management based on financial applications. Designing an online marketing system by conducting training and mentoring on the use of social media and optimizing strategies for using e-commerce applications.